Direct and Inverse Problems of Baire Classification of Integrals Depending on a Parameter - Banakh, T. O.; Kutsak, S. M.; Maslyuchenko, V. K.; Maslyuchenko, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We study the problem of the Baire classification of integrals g (y) = (If)(y) = ∫ X f(x, y)dμ(x), where y is a parameter that belongs to a topological space Y and f are separately continuous functions or functions similar to them. For a given function g, we consider the inverse problem of constructing a function f such that g = If. In particular, for compact spaces X and Y and a finite Borel measure μ on X, we prove the following result: In order that there exist a separately continuous function f : X × Y → ℝ such that g = If, it is necessary and sufficient that all restrictions g| Y n of the function g: Y → ℝ be continuous for some closed covering { Y n : n ∈ ℕ} of the space Y.